Edukasi Pencegahan dan Penanganan Diare dengan Pemanfaatan Teh Daun Jambu Biji (Psidium Guava) - Miko Eka Putri; Mila Triana Sari; Irene Katriani; Della Anggita; Vevi Suryenti (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Diarrhea is a condition where a person defecates with a soft or liquid consistency, it can even be just water and the frequency is more often (usually 3 times or more) in one day. This service aimed to provide education to the public on how to prevent diarrhea and manage diarrhea by using guava leaf tea. This Education has been done on August 5, 2022 at RT 07 Legok Village, Jambi City. The series of service activities are as follows: 1). The pretest which was carried out before the implementation of the counseling was carried out precisely at 16.00 WIB (for 5 minutes) 2). Providing education about the prevention and treatment of diarrhea by conducting discussions and demonstrations on making guava leaf tea for 30 minutes (25 minutes for education and 5 minutes for questions and answers). and 3)., 3). Post test, carried out 5 minutes after the implementation of education. The result of this activity was an increase in knowledge about diarrhea and its handling using guava leaf tea from the average knowledge before service was carried out of 6.7 increased to 8.6 after education and demonstrations were carried out. For this reason, it is hoped that the Legok community, especially RT 07, will treat diarrhea by utilizing guava tea leaves